Inseminação artificial em bovinos - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The objective of this experiment was to compare the efficiency of conventional Artificial Insemination (AI) and bulls re-pass on pregnancy rates of 4,069 cows for six breeding seasons between the years 2008 and 2013 on a property in the town of Don Pedrito in Rio Grande do Sul the animals were divided into annual and subjected to the technique of conventional artificial insemination and reviewed with lots bulls. Pregnancy diagnosis was performed by ultrasound pregnancy rates of the two groups IA and natural breeding subjected to chi-square method and SPSS® Program to verify their distribution among the years. There was no significant difference in pregnancy rates in the years evaluated, and verified an average rate of 75% during the study period. Pregnancy rates per artificial insemination had an average of 61% and the average transfer of 14%.
Keywords: Biotecnologia; Fertilidade; Melhoramento animal; Taxa de prenhez; Animal improvement; Biotechnology; Fertility; Pregnancy rate; CNPQ::CIENCIAS AGRARIAS